Disease site as a determinant of survival outcome in patients with primary cutaneous peripheral T-cell lymphoma, unspecified: an analysis of 4057 cases from the US National Cancer Database. Issue 9 (2nd September 2018) - Su, Chang; Nguyen, Kevin A.; Bai, Harrison X.; Cao, Ya; Tao, Yongguang; Karakousis, Giorgos; Zhang, Paul J.; Zhang, Guiying; Xiao, Rong
Abstract: Primary cutaneous peripheral T-cell lymphoma, unspecified (PCPTL) accounts for <6% of cutaneous T-cell lymphoma cases. Due to its rarity, no large study exists in the literature on PCPTL. Among 4057 patients with PCPTL diagnosed from 2004 to 2014 in the National Cancer Database, 428, 913, 517, 754, and 1435 had lesions localized primarily to the upper extremity, head and neck, lower extremity, trunk, and overlapping lesion or unspecified site, respectively. PCPTL that primarily involved the head and neck had the longest overall survival (OS), followed by PCPTL that primarily involved the trunk, upper extremity, and lower extremity. Patients with lesions localized to the lower extremity had significantly shorter OS when compared to those with disease localized to other primary sites after adjusting for confounding factors. The difference in OS among disease sites was only significant in stage I disease, but not higher stages, and persisted in younger patients.